Identification of new heading date determinants in wheat 5B chromosome. Issue 1 (January 2016) - Kiseleva, Antonina; Shcherban, Andrey; Leonova, Irina; Frenkel, Zeev; Salina, Elena
Abstract Background Variability of heading date may assist in wheat adaptation to local environments. Thereafter, discovery of new heading date determinants is important for cereal improvement. In this study we used common wheat cultivar Chinese Spring (CS) and the substitution line of CS with 5B chromosome fromT. dicoccoides (CS-5Bdic), different in their heading date by two weeks, to detect determinants of heading date on 5B chromosome. Results The possible influence of theVRN-B1 gene, the most powerful regulator of flowering, located on 5B chromosome, to differences in heading time between CS and CS-5Bdic was studied. The sequencing of this gene from CS-5Bdic showed that an insertion of a nucleotide triplet produced an additional amino acid in the corresponding protein. No changes in the transcription levels of each homoeologousVRN-1 loci were found in CS-5Bdic by comparison with CS. To ascertain the loci determining heading date difference, a set of 116 recombinant inbred 5В chromosomal lines as a result of hybridization of CS with CS-5Bdic were developed and their heading dates were estimated. Using the Illumina Infinium 15 k Wheat platform, 379 5B-specific polymorphic markers were detected and a genetic map with 82 skeletal markers was constructed. Phenotype (heading date) – genotype association analysis revealed seventy eight markers in pericentromeric region of 5B chromosome significantly associated with heading date variation. Based on this estimation and synteny with model crop genomes we identified the three best candidate genes:WRKY, ERF/AP2 andFHY3/FAR1 . Conclusions We supposed that the difference in activity ofWRKY, ERF/AP2 and/orFHY3/FAR1 transcription factors between CS and CS-5Bdic to be a probable reason for the observed difference in heading dates. Data obtained in this study provide a good basis for the subsequent investigation of heading time pathways in wheat.